Exogenous plasmid capture to characterize tetracycline-resistance plasmids in sprouts obtained from retail in Germany - Stein, Maria; Brinks, Erik; Habermann, Diana; Cho, Gyu-Sung; Franz, Charles M. A. P. (Frontiers in Microbiology, 2025)
This study aimed to characterize antibiotic-resistance plasmids present in microorganisms from sprout samples using exogenous plasmid capture. Fresh mung bean sprouts were predominantly colonized by bacteria from the phyla Proteobacteria and Bacteroidetes. To capture plasmids, a plasmid-free Escherichia (E.) coli CV601 strain, containing a green fluorescent protein gene for selection, was used as the recipient strain in exogenous plasmid capture experiments. Transconjugants were selected on media containing cefotaxime or tetracycline antibiotics. While no cefotaxime-resistant transconjugants were obtained, 40 tetracycline-resistant isolates were obtained and sequenced by Illumina NextSeq short read and Nanopore MinION long read sequencing. Sequences were assembled using Unicycler hybrid assembly. Most of the captured long plasmids carried either the tet(A) or tet(D) resistance gene, belonged to the IncFI or IncFII replicon types, and were predicted as conjugative. While the smaller plasmids contained the tet(A) tetracycline resistance gene as well as additional quinolone (qnrS1), sulfonamide (sul1) and trimethoprim (dfrA1) resistance genes, the larger plasmids only contained the tet(D) resistance gene. An exception was the largest 192 kbp plasmid isolated, which contained the tet(D), as well as sulfonamide (sul1) and streptomycin (aadA1) resistance genes. The smaller plasmid was isolated from different sprout samples more often and showed a 100% identity in size (71,155 bp), while the 180 kbp plasmids showed some smaller or larger differences (in size between 157,683 to 192,360 bp). This suggested that the plasmids obtained from the similar sprout production batches could be clonally related. Nanopore MinION based 16S metagenomics showed the presence of Enterobacter (En.) cloacae, En. ludwigii, En. kobei, Citrobacter (C.) werkmanii, C. freundii, Klebsiella (K.) oxytoca and K. pneumonia, which have previously been isolated from fresh produce in Germany. These bacteria may harbor antibiotic resistance genes on plasmids that could potentially be transferred to similar genera. This study demonstrated that bacteria present in sprouts may act as the donors of antibiotic resistance plasmids which can transfer resistance to other bacteria on this product via conjugation.